WATER IRRIGATION EXPERT SYSTEM (WIES): AN EXPERT SYSTEM FOR MANAGEMENT OF WATER - Anjeev Kumar Singh, Dr. Pawan Kr. Choudhary (International Journal of Research Science and Management, 2015)
Expert System is one of the applications of Artificial Intelligence. Expert system is a computer program that is different from the conventional computer program. Expert Systems are also referred as knowledge based systems. The development of any expert system must help the end-user and domain knowledge person. Efficient management of water is very important to achieve optimal utilization of available water resources. In field of Irrigation Management the most important tasks are Selection of crops, accurate estimation of irrigation demands and operation. This paper deals the suitability of application of expert system technology in agriculture and proposes the development of knowledge-based expert system name WIES (Water Irrigation Expert System) for the effective irrigation management of the water. The proposed system uses the knowledge of moisture levels in the soil to get the time of irrigation. The system has been developed in the Net Beans Java (GUI) application. The results given by the system have been found to be consistent and sound.